Barriers to Acceptance of Post‑partum Family Planning among Women in Montserrado County, Liberia (2018)
Background: Maternal mortality in Liberia is one of the highest in Sub Saharan Africa. Post partum family planning (PPFP) can reduce the risk of maternal mortality by preventing unwanted and closely spaced pregnancies. Yet, the uptake of PPFP is low in Liberia. Objective: We investigated the barriers to acceptance of PPFP use among women in Montserrado County, Liberia. Materials and Methods: Across-sectional facility based survey was conducted using a multistage sampling technique to select 378 women within 12 months’ post partum period. Results: About half of our respondents were were married, 66.4% had at least secondary education and 92.1% were Christians. The most commonly reported barriers were the fear of side effects(22.0%) and the post partum abstinence (22.2%). Binary logistic regression analysis showed that being within the early post partum period, i.e., within the first 6 months (adjusted odds ratio [AOR] = 0.23, 95% confidence interval [CI] [0.09–0.60] and lack of access to PPFP [AOR = 0.22, 95% CI [0.09–0.52]). Importantly, women who were married [AOR = 1.686, 95% CI (0.65, 4.36)] and those who were aware of PPFP [AOR 3.69, 95% CI (1.224, 11.096)] increased the likelihood of using PPFP. Conclusion: Important barriers to the utilisation of PPFP in Liberia were being within early post partum period, lack of access and awareness of PPFP including myths and misconception. Therefore, health communication targeting mothers for PPFP at every contact with maternal and childcare services should be encouraged